2009
DOI: 10.1158/0008-5472.can-09-1354
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Applied Ecology: Cancer Control Using an Evolutionary Double Bind

Abstract: Because the metastatic cascade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 41 publications
4
161
0
1
Order By: Relevance
“…Other authors have suggested that under conditions of tumor genetic instability, heterogeneous tumors contain populations of one or more resistant clones (44,45). These resistant subpopulations can be residual compared with other clones in a pretreated tumor due to the phenotypic cost associated with chemoresistance, but could get favored when the anticancer therapy is applied (46). This hypothesis is supported by our results.…”
Section: Discussionsupporting
confidence: 87%
“…Other authors have suggested that under conditions of tumor genetic instability, heterogeneous tumors contain populations of one or more resistant clones (44,45). These resistant subpopulations can be residual compared with other clones in a pretreated tumor due to the phenotypic cost associated with chemoresistance, but could get favored when the anticancer therapy is applied (46). This hypothesis is supported by our results.…”
Section: Discussionsupporting
confidence: 87%
“…Should treatments thus be tailored to allow survival of "nicer" cancer cells, maintaining on the long run such situations by"adaptive therapy", as proposed by Robert Gatenby [96,97,98]? These are some of the questions control scientists are confronted with.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Adaptive therapy [107] aims to use eco-evolutionary dynamics and Darwinian principles to create therapies that anticipate the evolutionary responses of the tumour cells. Such therapies might create evolutionary double-binds [108] where different therapies elicit resistance strategies that drive the cancer cells into the arms of the other therapy [109] and that treat the tumour as a community of coexisting cancer species rather than as a single entity. When 'treating to kill' cannot work, it may be possible to use adaptive therapies to 'treat to contain'.…”
Section: Cancer As An Evolutionary Gamementioning
confidence: 99%